Development of three new multidimensional measures to assess household food insecurity resilience in the United States - Calloway, Eric E.; Carpenter, Leah R.; Gargano, Tony; Sharp, Julia L.; Yaroch, Amy L. (Frontiers in Public Health, 2022)
This study aimed to develop and test novel self-administered measures (Absorptive capacity, Adaptive capacity, and Transformative capacity) of three aspects of a household’s resilience to financial shocks (e.g., job loss) that can increase food insecurity risk. Measures were piloted in a convenience sample of households at risk for food insecurity in the United States. The survey included the new measures, validation variables (financial shock, household food security, general health, personal resilience to challenges, and financial wellbeing), and demographic questions. Exploratory factor analysis was used to assess dimensionality, internal consistency was assessed (Cronbach’s alpha (CA)), and construct validity was assessed (Spearman’s correlation). Also, brief screener versions of the full measures were created. Participants in the analytic samples (n=220-394) averaged 44 years old, 67% experienced food insecurity, 47% had a high school diploma or less, 72% were women, and the sample was racially/ethnically diverse. Scores for Absorptive capacity (1 factor; CA=0.70; Mean=1.32 (SD=0.54)), Adaptive capacity (3 factors; CAs 0.83-0.90; Mean=2.63 (SD=0.85)), and Transformative capacity (3 factors; CAs 0.87-0.95; Mean=2.70 (SD=1.10)) were negatively associated with financial shocks (-0.221 - -0.307) and positively associated with food insecurity (0.310-0.550) general health (0.255-0.320), personal resilience (0.231-0.384), and financial wellbeing (0.401-0.474). These findings are encouraging and support reliability and validity of these new measures within this sample. Following further testing, such as Confirmatory Factor Analysis in future samples, these measures may prove useful for needs assessments, program evaluation, intake screening, and research/surveillance. Widespread adoption in the future may promote a more comprehensive understanding of the food insecurity experience and facilitate development of tailored interventions on upstream causes of food insecurity.